Convergence and Asymmetry: Observations on the Current State of Jewish-Christian Dialogue - Vincent, Alana M. (Interreligious Studies and Intercultural Theology, 2020)
Drawing on a survey of forty-five statements on the status of JewishChristian dialogue, this article argues that the theme of convergence which underlies a substantial portion of this dialogue programme arises from an asymmetric power relationship, in which Christian institutions have been insufficiently attentive to the issue of Jewish self-understanding.